PREDICTING RETAIL INVESTORS’ INTENTION TO INVEST IN SOVEREIGN SUKUK: THEORY OF PLANNED BEHAVIOR - Maharani, Yasmin Putri; Qadri, Resi Ariyasa (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study seeks to predict the determinants of retail investors' intention to invest in Sovereign Sukuk within the framework of the Theory of Planned Behavior (TPB). The research model incorporates the antecedents of attitudes, subjective norms, and perceived behavioural control. A quantitative approach was used to test the factors from the literature through a survey. Convenience sampling produced a sample of 811 respondents, categorised into existing and potential investors. The results of the SEM-PLS analysis indicate that attitude, subjective norms, and perceived behavioural control have a significant positive relationship with the intention to invest in Sovereign Sukuk across both groups of investors. For existing investors, knowledge and religious factors positively impact investment intention, while patriotism, risk, yield, and tradability have no effect. Normative beliefs positively influence subjective norms but pressure from religious figures and influencers does not. Self-efficacy and facilitating conditions positively affected perceived behavioural control. For potential investors, patriotism, knowledge, risk, yield, and tradability have a positive impact, whereas religious factors do not. Both normative beliefs and pressures from religious figures and influencers positively influence investment intentions. Self-efficacy and facilitating conditions positively affect perceived behavioural control. These findings are crucial for policymakers to develop strategies to expand their investors based on the key determinants of investment intention.